Using Participatory Video to Understand Diversity Among People With Dementia in Long‐Term Care. Issue 4 (January 2015) - Ludwin, Katherine; Capstick, Andrea
<x xml:space="preserve">Abstract</x> Within care organizations, "people with dementia" are often labeled as a homogenous group with little differentiating them from each other. This can mark them out as separate from and less capable than those without dementia. When individuals with dementia are described, understood, and related to in terms of their diagnosis, individuality may get lost. In this article, we seek to unsettle the socially constructed boundary between "people with dementia" and people without dementia. This is explored in the context of fieldwork we undertook as part of a Participatory Video project where we worked alongside people with a dementia diagnosis to co‐create short films about their interests and concerns. In the process of this work, we found that alternative unities emerged between ourselves and people with dementia, as the dementia label faded into the background and the person, with all his or her diverse interests and life experiences, came to the fore. We found ourselves building rapport and making connections with our research participants, a diverse group of individuals whose life experiences, outlooks, and experiences were simultaneously unique to them but also shared in many ways between themselves, and with us. As we spent time with participants in the communal lounge, in the adjoining day center, walking the hallways, out in the garden, or in individual apartments when invited, we found that people shared a wealth of information with us: about how they were feeling, things they liked, things they had done, instances of trauma, as well as some of their happiest times.